SIKAP KONSUMEN TERHADAP PRODUK UNGGULAN SEKTOR MAKANAN KOTA MATARAM (STUDI PADA PRODUK TAHU ABIAN TUBUH) - H M Ilhamuddin; Hj Santi Nururly; Rusminah Rusminah (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2019)
This research is aimed at determining the attitude of consumers towards one of the superior products of Mataram city, that is tahu Abian Tubuh. The research is descriptive which using sample survey method. In order to answer the problem proposed, the analytical tool is Ideal-Point Model. The model measures a difference between what is desired and what is perceived by consumers. The result of this study shows that consumer attitudes are very good. It is indicated by attitude value of 13,764 which is lied at the highest interval in linear numerical scale 0 < Ab < 22,56 (very good). It means that the Tahu Abian Tubuh is in accordance with consumer’s desire. Key words: consumer’s attitude, tahu Abian Tubuh.